A Project-Based Learning Approach for Chemical Engineering Students Involving Waste Cooking Oil Biodiesel Production for Portable Stove Application - Rahma Amalia; Rosmawati Sipayung; Nazarudin (Postgraduate, University of Mataram, 2025)
This study implemented project-based learning in a bioenergy engineering course at the Pondok Meja Campus, Universitas Jambi, involving 17 chemical engineering students during the first semester of the 2024/2025 academic year. Conducted over 13 weeks, the project involved biodiesel production from waste cooking oil using NaOH and CaO catalysts, followed by fuel application in a portable stove. The highest biodiesel yield was 92.3% (3% NaOH, 1:6 oil-to-methanol) and 42.0% (6% CaO, 1:12). The density ranged from 0.87 to 0.89 g/cm³, with stove fuel consumption rates of 0.0607 ml/s (NaOH) and 0.0412 ml/s (CaO). Evaluation involved class participation, lab performance, product presentation, and final reporting, yielding an overall project score of 87/100. Student feedback showed high agreement (mean 4.45/5) in teamwork, problem solving, critical thinking, time management, and proactiveness, supported by lecturer assessments (13.1/15). Challenges included equipment limitations and time constraints, yet all groups completed the project on time. This hands-on approach effectively achieved subject-specific and transferable skills, fostering engineering competence and readiness for real-world bioenergy challenges.